Extraction of potassium from some kaolinitic soils of the tropics - Pleysier, J.L.; Janssens, J.; Cremers, A. (1988)
Three methods for soil potassium extraction (M NH4OAc pH 7, 0.01 M AgTU and 30 % hot H2SO4) were compared for a variety of kaolinitic soils of the tropics. The AgTU‐extractable K was much higher than the M NH4OAc‐extractable K when vermiculite clay was present in the soil. The correlation between both was given by an R value of 0.937. The amounts of K extracted by 0.01 M AgTU and by hot H2SO4 were approximately the same. The R value for these two methods was 0.843. It is suggested that the AgTU extractant could be used for determination of plant‐available K in soil and for testing for the presence or absence of vermiculite clay in soils.